Magel2 in hypothalamic POMC neurons influences the impact of stress on anxiety-like behavior and spatial learning associated with a food reward in male mice - Lee, Sangbhin; Jo, Young-Hwan (Frontiers in Neural Circuits, 2025)
IntroductionPrader-Willi syndrome (PWS) results from a lack of expression in several paternally inherited, imprinted contiguous genes. Among the genes inactivated in PWS, the Magel2 gene is considered a significant contributor to the etiology of the syndrome. The loss of the Magel2 gene causes abnormalities in growth and fertility and increased adiposity with altered metabolism in adulthood, which aligns with some of the pathologies observed in PWS. Given that anxiety is a prominent phenotypic behavior in PWS, we investigate the role of the Magel2 gene, particularly in hypothalamic POMC neurons innervating the medial amygdala (MeA), in the behavioral phenotypes associated with Prader-Willi Syndrome (PWS).MethodsIn this study, we used a retrograde AAV containing the Cre recombinase under the control of neuronal Pomc enhancers to genetically eliminate the Magel2 gene in MeA-innervating ARCPomc neurons.ResultsBoth male and female mice lacking the Magel2 gene in MeA-innervating ARCPomc neurons display no alterations in anxiety-like behavior during the open field test, light/dark test, and elevated plus maze test in the absence of exposure to acute stress. However, male mice with a Magel2 gene deletion in these particular neurons exhibit increased stress-induced anxiety-like behavior and reduce motivation/spatial learning, while female mice do not show these behavioral changes. Our results suggest that the Magel2 gene in ARCPomc neurons, especially in males, influences the impact of stress on anxiety-like behavior and spatial learning deficits associated with a food reward.DiscussionWith the recent approval of a novel treatment for hyperphagia in PWS by the FDA that seems to target the hypothalamic melanocortin system, understanding the cellular mechanisms by which MAGEL2 in ARCPomc neurons innervating the MeA regulates emotional behaviors might help the development of new therapeutic strategies for addressing mental illness in individuals with PWS.